Continuity of Care (COC) pada Ny.L Umur 26 Tahun G2P1A0 di PMB X - Yulianti, Rizkhiana; Hapsari Windayanti (Universitas Ngudi Waluyo, 2025)
Continuous midwifery care (continuity of care) is the provision of midwifery care starting from pregnancy, childbirth, postpartum, neonates until deciding to use family planning (KB). This study started from November-April 2025, the research instrument used Varney's 7-step documentation and SOAP. By conducting Pregnancy Visits (ANC) on Mrs.